Landschaftsverständnisse in der Landschaftsplanung. Eine semantische Analyse der Verwendung des Wortes „Landschaft“ in kommunalen Landschaftsplänen - Wojtkiewicz, Wera; Heiland, Stefan (Raumforschung und Raumordnung | Spatial Research and Planning, 2012)
The meaning ascribed to the concept of “landscape” and the idea about how “landscape” is constituted, is a basis for setting up goals and measures concerning all natural assets in landscape plans, as e.g. soil, water or landscape scenery. Current research does not sufficiently address the question of how landscape plans refer to the concept of landscape and which ideal types of landscapes determine planning processes. This paper will shed light on the ideas about the use and shape of landscape, which are conveyed through local landscape plans. Therewith we are aiming to determine the role that landscape planning plays for the social construction of landscape. The research pursues a hermeneutic approach and is conducted by means of a qualitative content analysis of municipal landscape plans created between 1993 and 2010 in various regions of Germany. The semantic analysis of the word landscape allows statements on ideas of how “landscape” should look like. This image equates to a narrow notion of landscape, implying that mainly areas characterized by traditional, peasant cultivation are interpreted as “landscape”. The identified notion of landscape is orientated on conservation rather than development. The current development of landscape and resulting imprint on an area is rarely being taken into account in a positive manner.